2017
DOI: 10.1080/13696998.2016.1269016
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of inadequate symptom control among US commercially insured patients with irritable bowel syndrome with diarrhea

Abstract: Inadequate symptom control associated with available IBS-D therapies represents a significant economic burden for both payers and IBS-D patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…IBS-D, is associated with reduced quality of life 2,3 and increased healthcare costs. 4,5 In one study, 76.5% of 179 patients with IBS reported impaired daily activity (ie, ≥5 of 10 domains examined: job/school performance, social activity, physical activity, physical appearance, household activities, sexual activity, leisure activity, travel, eating alone, and eating in groups), with social activity impaired in 80% of patients and job/school performance in 72%. 6 In the United States, IBS is usually managed on an outpatient basis.…”
Section: Ibs Includingmentioning
confidence: 99%
See 1 more Smart Citation
“…IBS-D, is associated with reduced quality of life 2,3 and increased healthcare costs. 4,5 In one study, 76.5% of 179 patients with IBS reported impaired daily activity (ie, ≥5 of 10 domains examined: job/school performance, social activity, physical activity, physical appearance, household activities, sexual activity, leisure activity, travel, eating alone, and eating in groups), with social activity impaired in 80% of patients and job/school performance in 72%. 6 In the United States, IBS is usually managed on an outpatient basis.…”
Section: Ibs Includingmentioning
confidence: 99%
“…IBS is further categorised by its predominant bowel habit, including diarrhoea‐predominant IBS (IBS‐D; >25% Bristol Stool Scale form types 6 or 7 and <25% Bristol Stool Scale form types 1 or 2), constipation‐predominant IBS (>25% Bristol Stool Scale form types 1 or 2 and <25% Bristol Stool Scale form types 6 or 7), or mixed form IBS (>25% Bristol Stool Scale form types 1 or 2 and >25% Bristol Stool Scale form types 6 or 7) . IBS, including IBS‐D, is associated with reduced quality of life and increased healthcare costs …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate of IBS in the Korean population ranges from 9%-9.6% [2,3]. Repeated abdominal pain and bowel movements lead to a loss in quality of life (QOL), and an increase in economic burden due to the high medicinal costs associated with treatment through repeated improvement and deterioration; thus, it is necessary to improve patients' QOL through active treatment [4,5]. Some medical research in Korea has been conducted on IBS treatment using general acupuncture, moxibustion, cupping, phamarcoacupuncture, and herbal medicine.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Traditionally, pharmacologic management has primarily involved addressing specific symptoms, with limited evidence that many existing treatments effectively control the multiple symptoms of IBS-D. 13 In one study, more than half of patients with IBS-D reported inadequate symptom control with the currently available medication options. 14 IBS-D is associated with a substantial economic burden in terms of its impact on work productivity and healthcare resource use, and patients with inadequate symptom control use significantly more healthcare resources and incur significantly greater costs. 14,15 Eluxadoline, a mixed μ-and κ-opioid receptor agonist and δopioid receptor antagonist approved for the treatment of IBS-D in adults, 16 has demonstrated efficacy for multiple IBS-D symptoms, based on 2 large Phase 3 trials.…”
Section: Introductionmentioning
confidence: 99%
“…14 IBS-D is associated with a substantial economic burden in terms of its impact on work productivity and healthcare resource use, and patients with inadequate symptom control use significantly more healthcare resources and incur significantly greater costs. 14,15 Eluxadoline, a mixed μ-and κ-opioid receptor agonist and δopioid receptor antagonist approved for the treatment of IBS-D in adults, 16 has demonstrated efficacy for multiple IBS-D symptoms, based on 2 large Phase 3 trials. Significantly greater proportions of patients receiving eluxadoline were responders vs placebo based on a primary composite endpoint consisting of simultaneous reduction in abdominal pain and improvement in stool consistency.…”
Section: Introductionmentioning
confidence: 99%